Laporan Sub Proyek Riset Institusional, Fakultas Sosial dan Politik, Universitas Negeri Jember (Sub Proyek Riset Institusional, Fakultas Sastra, Universitas Negeri Jember, 1982)
Agricultural extension, village cooperatives, small-scale industry, social condition of women laborers; case studies in Kabupaten Jember, Jawa Timur.